Strategies for Enhancing Mathematical Creative Thinking in Elementary Schools: A Systematic Literature Review - Semi Semi; Zulherman Zulherman (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Mathematical creative thinking is an essential competency that should be developed in elementary school students to support higher-order thinking skills, problem-solving abilities, and readiness to face the challenges of the twenty-first century. Although various instructional strategies have been implemented to enhance this competency, the existing research findings remain fragmented, highlighting the need for a systematic synthesis. This study aims to identify and analyze effective instructional strategies for improving elementary school students' mathematical creative thinking skills through a Systematic Literature Review (SLR). The literature search was conducted using Publish or Perish with Google Scholar as the primary database. A total of 500 articles were initially identified and screened based on the PRISMA 2020 guidelines and predetermined inclusion criteria. The screening process resulted in nine eligible articles for further analysis. The findings indicate that instructional strategies such as Realistic Mathematics Education (RME), Problem-Based Learning (PBL), Brain-Based Learning, the Open-Ended approach, and other innovative learning methods consistently contribute to improving students' mathematical creative thinking skills. Overall, student-centered, contextual, and problem-based learning approaches were found to be the most effective characteristics of instructional strategies for fostering mathematical creativity in elementary school students.